The challenges and countermeasures of MOOC to the teaching reform in universities - Jin, Yongxian; Jin, Mengqi (IJRDO- Journal of Educational Research, 2018)
As an emerging curriculum model, MOOC (Massive Open Online Course) has a grea impact on traditionaluniversity teaching by providing free teaching resources, realizing complete learning experience, and timely interaction tostudents.Through the overview of MOOC, this paper analyze many challenges to the reform of university teaching thatMOOC brings. On this basis, it puts forward the strategies that should be taken in the teaching reform in universitie